Cardiovascular Rehabilitation for transient ischaemic Attack and Mild Stroke: the CRAMS effectiveness-implementation hybrid study protocol - Nicole Freene; Hannah Wallett; Allyson Flynn; Elisabeth Preston; Shahla Cowans; Christian Lueck; Theophile Niyonsenga; Itismita Mohanty; Rachel Davey (BMC, 2022)
Abstract Background Internationally, stroke and cardiac rehabilitation clinicians agree that current cardiac rehabilitation models are a suitable secondary prevention program for people following a transient ischaemic attack (TIA) or mild stroke. There is strong evidence for exercise-based cardiac rehabilitation in people with heart disease, however, the evidence for cardiac rehabilitation post-TIA or stroke is limited. Here we will explore the effectiveness and implementation of an integrated (TIA, mild stroke, heart disease) traditional exercise-based cardiovascular rehabilitation (CVR) program for people with TIA or mild stroke over 6-months. Methods This type 1 effectiveness-implementation hybrid study will use a 2-arm single-centre assessor-blind randomised controlled trial design, recruiting 140 participants. Adults who have had a TIA or mild stroke in the last 12-months will be recruited by health professionals from hospital and primary healthcare services. Participants will be assessed and randomly allocated (1:1) to the 6-week CVR program or the usual care 6-month wait-list control group. Distance completed in the 6-min walk test will be the primary effectiveness outcome, with outcomes collected at baseline, 6-weeks (complete CVR) and 6-months in both groups. Other effectiveness outcome measures include unplanned cardiovascular disease-related emergency department and hospital admissions, daily minutes of accelerometer moderate-to-vigorous physical activity, body mass index, waist circumference, blood pressure, quality of life, anxiety and depression. Implementation outcomes will be assessed using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework, including a cost-effectiveness analysis. Semi-structured interviews will be conducted with participants and CVR program health professionals, investigating the acceptability, value, and impact of the CVR program. Qualitative analyses will be guided by the Consolidated Framework for Implementation Research. Discussion Few studies have assessed the effectiveness of cardiac rehabilitation for people with TIA and mild stroke, and no studies appear to have investigated the cost-effectiveness or implementation determinants of such programs. If successful, the CVR program will improve health outcomes and quality of life of people who have had a TIA or mild stroke, guiding future research, policy, and clinical practice, reducing the risk of repeat heart attacks and strokes for this population. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12621001586808 , Registered 19 November 2021.